2005
DOI: 10.1074/jbc.m505622200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling and Site-directed Mutagenesis of Plant Chloroplast Monogalactosyldiacylglycerol Synthase Reveal Critical Residues for Activity

Abstract: Monogalactosyldiacylglycerol (MGDG), the major lipid of plant and algal plastids, is synthesized by MGD (or MGDG synthase), a dimeric and membrane-bound glycosyltransferase of the plastid envelope that catalyzes the transfer of a galactosyl group from a UDP-galactose donor onto a diacylglycerol acceptor. Although this enzyme is essential for biogenesis, and therefore an interesting target for herbicide design, no structural information is available. MGD monomers share sequence similarity with MURG, a bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 60 publications
5
31
0
Order By: Relevance
“…Upon phosphate deprivation, DGDG is exported outside plastids to the plasma membrane (60) and the mitochondria (31). No MGDG synthase or DGDG synthase homologous sequences could be detected in the genome of some plastid-containing organisms, such as Euglena, in which MGDG and DGDG are well-established constituents (61), suggesting that their synthesizing enzymes might have strongly diverged during evolution. Searching both Toxoplasma and Plasmodium databases did not reveal any gene candidate for MGDG synthesis, leaving the question of the monogalactolipid-synthesizing enzymes unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Upon phosphate deprivation, DGDG is exported outside plastids to the plasma membrane (60) and the mitochondria (31). No MGDG synthase or DGDG synthase homologous sequences could be detected in the genome of some plastid-containing organisms, such as Euglena, in which MGDG and DGDG are well-established constituents (61), suggesting that their synthesizing enzymes might have strongly diverged during evolution. Searching both Toxoplasma and Plasmodium databases did not reveal any gene candidate for MGDG synthesis, leaving the question of the monogalactolipid-synthesizing enzymes unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…The MGD enzymes synthesizing the lipid substrate GalDAG in the preceding pathway are of a similar GT-B fold (22) but are grouped in another CAZy family (GT-28). Several sequences features are conserved between the three isoenzymes, including a number of Trp residues on the potential interface-binding surfaces (72).…”
Section: Discussionmentioning
confidence: 99%
“…The MPEx profile for atC-DGD1 was very similar to the profile of atDGD2, including the existence of all Trp residues, which are totally conserved (data not shown). This feature can vary among membrane-bound GTs; the strongly binding alMGS (54) has only one Trp in the full sequence, whereas high Trp numbers were found in the sequences of atMGD2 and atMGD3 and a lower number in atMGD1, soMGD1 (the spinach (Spinacia oleracea) homologue) (22), and MurG (55). Given that Trp has the strongest bilayer interface affinity of all amino acid residues (56), the numbers and localization of Trp residues in these monotopic proteins must clearly be important.…”
Section: Journal Of Biological Chemistry 6675mentioning
confidence: 99%
See 1 more Smart Citation
“…Native and recombinant MGD1 are known to be active as homodimers (5). Each MGD1 monomer is likely to be organized in two Rossmann folds (N-and C-domains) (7). Visualization of surface hydrophobic regions suggested that MGD1 interacts with the membrane surface by its N-domain, whereas the C-domain protrudes above the membrane.…”
mentioning
confidence: 99%